Christianity and critical race theory : a faithful and constructive conversation - Romero, Robert Chao, 1972-; Liou, Jeff M., 1979- (Grand Rapids, MI. Baker Academic, 2023)
"Critical Race Theory (CRT) is often poorly understood and unfavorably characterized. This accessibly written book offers a critical yet sympathetic introduction to CRT, bringing it into conversation with Christian theology and ministry practice"--
Introduction: critical race theory in Christianity -- Creation: community cultural wealth and the glory and honor of the nations -- Fall: sin and racism--the ordinary businesses of society -- Redemption: critical race theory in institutions -- Consummation: the beloved community -- Conclusion: made to be image bearers
Includes bibliographical references (page 181-188) and index
Keywords: Critical race theory -- Religious aspects -- Christianity; Race relations -- Religious aspects -- Christianity; Discrimination -- Religious aspects -- Christianity; Christian sociology; United States -- Race relations